A Survey on Premature Death in Early Chicks and the Assessment of the Responsible determinants: A Case Study in the Afigya Sekyere South District of the Ashanti Region of Ghana - Appiah, Michael Osei (International Journal of Environment, Agriculture and Biotechnology, 2019)
Objective: An investigation was carried out in the Afigya-Sekyere South District to determine the rate of early chick mortality in the first four weeks and the factors that may have caused this. Methods: Structured questionnaires and personal observations were used to obtain information from twenty-eight (28) farm managers. Results: The study revealed that mortality was higher in the first and second week with an average mean mortality of 11.39 and 6.43 respectively. According to the farm managers, all the mortality reported was a result of disease infection. Statistical analysis also depicted that the source of the day-old chicks (local or imported), experience and educational level of the managers and the type of breed were the factors that affected disease occurrence on the farm which consequently caused early chick mortality. Conclusion: Diseases such as Gumboro and Coccidiosis were reported with a percentage of 35.7% and 39.3% respectively and these caused a mortality percentage of 33.86% and 36.99%. The studies further revealed that mortality increased with a decrease in the inefficiency of the managers. Statistical analysis also showed that local chicks were associated with higher mortality recording 0.80% as compared to 0.31% of the imported chicks in the first week. Mortality was also associated with the type of breed, with the Bovane black recording the highest percentage in all the four weeks recording 2.34% and 0.92% in the first and second week respectively.